Redox States of Protein Cysteines in Pathways of Protein Turnover and Cytoskeleton Dynamics Are Changed with Aging and Reversed by Slc7a11 Restoration in Mouse Lung Fibroblasts. (8th June 2020) - Zheng, Yuxuan; Merchant, Michael L.; Burke, Tom J.; Ritzenthaler, Jeffrey D.; Li, Ming; Gaweda, Adam E.; Benz, Frederick W.; Roman, Jesse; Watson, Walter H.
Abstract : Slc7a11 is the key component of system Xc -, an antiporter that imports cystine (CySS) and exports glutamate. It plays an important role in cellular defense against oxidative stress because cysteine (Cys), reduced from CySS, is used for and limits the synthesis of glutathione (GSH). We have shown that downregulation of Slc7a11 is responsible for oxidation of extracellular Cys/CySS redox potential in lung fibroblasts from old mice. However, how age-related change of Slc7a11 expression affects the intracellular redox environment of mouse lung fibroblasts remains unexplored. The purpose of this study is to evaluate the effects of aging on the redox states of intracellular proteins and to examine whether Slc7a11 contributes to the age-dependent effects. Iodoacetyl Tandem Mass Tags were used to differentially label reduced and oxidized forms of Cys residues in primary lung fibroblasts from young and old mice, as well as old fibroblasts transfected with Slc7a11. The ratio of oxidized/reduced forms (i.e., redox state) of a Cys residue was determined via multiplexed tandem mass spectrometry. Redox states of 151 proteins were different in old fibroblasts compared to young fibroblasts. Slc7a11 overexpression restored redox states of 104 (69%) of these proteins. Ingenuity Pathway Analysis (IPA) showed that age-dependent Slc7a11-responsive proteins were involved in pathways of protein translation initiation, ubiquitin-proteasome-mediated degradation, and integrin-cytoskeleton-associated signaling. Gene ontology analysis showed cell adhesion, protein translation, and organization of actin cytoskeleton were among the top enriched terms for biological process. Protein-protein interaction network demonstrated the interactions between components of the three enriched pathways predicted by IPA. Follow-up experiments confirmed that proteasome activity was lower in old cells than in young cells and that upregulation of Slc7a11 expression by sulforaphane restored this activity. This study finds that aging results in changes of redox states of proteins involved in protein turnover and cytoskeleton dynamics, and that upregulating Slc7a11 can partially restore the redox states of these proteins.